3D Spheroid Culture Enhances the Expression of Antifibrotic Factors in Human Adipose-Derived MSCs and Improves Their Therapeutic Effects on Hepatic Fibrosis. (28th February 2016) - Zhang, Xuan; Hu, Ming-Gen; Pan, Ke; Li, Chong-Hui; Liu, Rong
Abstract : Three-dimensional (3D) cell culture has been reported to increase the therapeutic potentials of mesenchymal stem cells (MSCs). However, the action mechanisms of 3D MSCs vary greatly and are far from being thoroughly investigated. In this study, we aimed to investigate the therapeutic effects of 3D spheroids of human adipose-derived MSCs for hepatic fibrosis. Our results showed that 3D culture enhanced the expression of antifibrotic factors by MSCs, including insulin growth factor 1 (IGF-1), interleukin-6 (IL-6), and hepatocyte growth factor (HGF). In vitro studies indicated conditioned medium of 3D cultured MSCs protected hepatocytes from cell injury and apoptosis more effectively compared with 2D cultured cells. More importantly, when transplanted into model mice with hepatic fibrosis, 3D spheroids of MSCs were more beneficial in ameliorating hepatic fibrosis and improving liver function than 2D cultured cells. Therefore, the 3D culture strategy improved the therapeutic effects of MSCs and might be promising for treatment of hepatic fibrosis.